2013
DOI: 10.1016/j.tecto.2012.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of a lithospheric tear fault (STEP) through the western boundary of the Calabrian accretionary wedge offshore eastern Sicily (Southern Italy)

Abstract: . Propagation of a lithospheric tear fault (STEP) through the western boundary of the Calabrian accretionary wedge offshore eastern Sicily (Southern Italy). Tectonophysics, Elsevier, 2013, 602, pp.141-152. 10.1016/j.tecto.2012

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 68 publications
2
90
0
Order By: Relevance
“…Refraction data of Dellong et al () also image a sharp ocean‐continent transition and the tabular architecture of the Ionian crust. Our section runs south of the Alfeo‐Etna fault system (Figures and ; Polonia et al, ) commonly interpreted as a STEP fault (Cernobori et al, ; Hirn et al, ; Argnani et al, ; see review in Gallais et al, ) and consequently does not show it. Polonia et al () suggested an alternative location for the STEP fault farther east, at the location of the Ionian fault system (Figures and ).…”
Section: Deep Structure Of the Ionian Basin And Of Its Margins: Regiomentioning
confidence: 87%
“…Refraction data of Dellong et al () also image a sharp ocean‐continent transition and the tabular architecture of the Ionian crust. Our section runs south of the Alfeo‐Etna fault system (Figures and ; Polonia et al, ) commonly interpreted as a STEP fault (Cernobori et al, ; Hirn et al, ; Argnani et al, ; see review in Gallais et al, ) and consequently does not show it. Polonia et al () suggested an alternative location for the STEP fault farther east, at the location of the Ionian fault system (Figures and ).…”
Section: Deep Structure Of the Ionian Basin And Of Its Margins: Regiomentioning
confidence: 87%
“…In the WL, across strike margin segmentation is more diffuse, and develops along a set of NNW-SSE trending fault systems (Hirn et al, 1997;Bianca et al, 1999 ;Nicolich et al, 2000;Chamot-Rooke et al, 2005;Argnani and Bonazzi, 2005;Del Ben et al, 2008;Rosenbaum et al, 2008;Polonia et al, 2011Polonia et al, , 2012Gallais et al, 2013). The main fault strand is represented by an active transtensive structure running from the Alfeo seamount to the offshore of the Mt.…”
Section: -Segmentation Of the Subduction Complex In The Ionian Seamentioning
confidence: 99%
“…At the Sicilian side, the passive margin is oriented parallel to the trace of the Taormina line, i.e., the Gallais et al, 2013) it is unclear whether it already existed before the Early-Middle Pliocene. We do not include it as a pre-existing feature in the models but, as we will see in the results below, this is inconsequential for the STEP propagation direction.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…This leads to uncertainty in defining the geodynamic setting. Open questions include the significance of the extension lying on a narrow zone near the Nebrodi Mountains, in a larger compressive domain characterizing central and western Sicily [e.g., Lavecchia et al , ; Billi et al , ; De Guidi et al , ], or again, the precise identification in northeastern Sicily of a faults‐wrenching system, which should be the shallow expression in the upper plate of a major lithospheric structure, accompanying the rollback of the Ionian slab along its edge [see, e.g., Polonia et al , ; Neri et al , ; Gallais et al , , and references therein]. Indeed, when subduction rollback occurs, lithospheric‐scale tear faults can develop between the adjacent portions of the subducting plate, accommodating different rates of slab rollback or decoupling the subducting lithosphere from the nonsubducting one.…”
Section: Introductionmentioning
confidence: 99%